Implementasi Sistem Informasi Rapor Digital (SIDORAL) Berbasis Web pada SMA Kapuas Pontianak - Anggi Basifatul Rahma; Erica Gracila Muntu; Eri Bayu Pratama; Lady Agustin Fitriana (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Report card management is a crucial part of the academic process in schools. However, at SMA Swasta Kapuas, the grade recapitulation process is still largely conducted semi-manually using separate spreadsheet applications. This mechanism triggers human error risks, slows down report card compilation, and complicates data retrieval. This study aims to build a web-based Digital Report Card Information System (SIDORAL) to integrate academic data management effectively. The system was developed using the CodeIgniter 4 Framework with Model-View-Controller (MVC) architecture and MySQL database. The software development methodology applied was Extreme Programming (XP), which includes planning, design, coding, and testing stages. The system functionality test was conducted using a structured testing method. The results show that SIDORAL successfully simplifies the integrated management of teacher, student, subject, and grade component data. Based on the testing phase results, all main features of the system were declared 100% valid and functioned properly without program logic errors. The implementation of SIDORAL is able to transform conventional grade data processing at SMA Swasta Kapuas into a secure digital system, thereby increasing distribution time efficiency and facilitating transparent delivery of learning outcomes information to students and parents.